2017
DOI: 10.1152/ajplung.00477.2016
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modification of β-catenin is associated with pathogenic fibroblastic changes in bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a common complication of premature birth. The histopathology of BPD is characterized by an arrest of alveolarization with fibroblast activation. The Wnt/β-catenin signaling pathway is important in early lung development. When Wnt signaling is active, phosphorylation of β-catenin by tyrosine kinases at activating sites, specifically at tyrosine 489 (Y489), correlates with nuclear localization of β-catenin. We examined fetal lung tissue, lung tissue from term newborns, and lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
2
29
0
2
Order By: Relevance
“…The endothelial-mesenchymal transition is a complex biological process in which endothelial cells lose their surface expression of endothelium-specific markers (e.g., CD31 and vonWillebrand factor) and acquire a mesenchymal phenotype and express markers like ␣-smooth muscle actin (SMA) (25). Exposure to hyperoxia leads to a profibrotic phenotype leading to an increase in myofibroblasts (30). The role of the endothelial-mesenchymal transition is known in lung diseases such as idiopathic pulmonary fibrosis (significant contribution to fibrosis and vascular regression) and pulmonary arterial hypertension (causing pulmonary vascular remodeling and endothelial dysfunction) (13,14,18).…”
Section: Introductionmentioning
confidence: 99%
“…The endothelial-mesenchymal transition is a complex biological process in which endothelial cells lose their surface expression of endothelium-specific markers (e.g., CD31 and vonWillebrand factor) and acquire a mesenchymal phenotype and express markers like ␣-smooth muscle actin (SMA) (25). Exposure to hyperoxia leads to a profibrotic phenotype leading to an increase in myofibroblasts (30). The role of the endothelial-mesenchymal transition is known in lung diseases such as idiopathic pulmonary fibrosis (significant contribution to fibrosis and vascular regression) and pulmonary arterial hypertension (causing pulmonary vascular remodeling and endothelial dysfunction) (13,14,18).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of b-catenin at tyrosine 489 promotes nuclear localization and transcription of Wnt target genes and has been previously reported to play a role in the fibroblastic changes associated with BPD. 14 In contrast, phosphorylation of b-catenin at other tyrosine sites, such as Y654, causes it to dissociate from E-cadherin and interact with other signaling complexes within the cell. 28 In particular, peb-catenin Y654 is involved with transforming growth factor-b1 signaling to promote epithelialmesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…13 We have previously identified the importance of bcatenin phosphorylation in the fibroblastic changes associated with BPD, specifically the nuclear accumulation of peb-catenin Y489 in alveolar epithelium and mesenchymal cells. 14 In this study, archived fetal tissue was used to describe the normal trajectory of b-catenin phosphorylation at two activating tyrosine sites across lung organogenesis and alveologenesis from 14 weeks' gestation to term. Furthermore, it was shown that there is reemergence of a distinct midgestational signature of b-catenin phosphorylation at tyrosine 489 and 654 in lungs with BPD and IPF, accompanied by increased expression of Wnt target gene AXIN2.…”
mentioning
confidence: 99%
“…Similarly, 3D cell culture technology has been used to study the effect of hypoxia in the context of ischemia in various cell types, including cardiomyocytes (152)(153)(154), astrocytes (155), endothelial cells (156), and hypoxia related to pulmonary fibrosis in fetal lung fibroblasts (157). Furthermore, the effects of both continuous hypoxia and IH on vascular sprouting has been explored in endothelial cells (158)(159)(160).…”
Section: D Cell Culturesmentioning
confidence: 99%